Noncanonical function of long myosin light chain kinase in increasing ER‐PM junctions and augmentation of SOCE. Issue 9 (9th August 2020) - Srivastava, Nityanand; Tauseef, Mohammad; Amin, Ruhul; Joshi, Bhagwati; Joshi, Jagdish Chandra; Kini, Vidisha; Klomp, Jennifer; Li, Weenan; Knezevic, Nebojsa; Barbera, Nicolas; Siddiqui, Shahid; Obukhov, Alexander; et al.
Abstract: Increased endothelial permeability leads to excessive exudation of plasma proteins and leukocytes in the interstitium, which characterizes several vascular diseases including acute lung injury. The myosin light chain kinase long (MYLK‐L) isoform is canonically known to regulate the endothelial permeability by phosphorylating myosin light chain (MLC‐P). Compared to the short MYLK isoform, MYLK‐L contains an additional stretch of ~919 amino acid at the N‐terminus of unknown function. We show that thapsigargin and thrombin‐induced SOCE was markedly reduced in Mylk‐L –/– endothelial cells (EC) or MYLK‐L‐depleted human EC. These agonists also failed to increase endothelial permeability in MYLK‐L‐depleted EC and Mylk‐L –/– lungs, thus demonstrating the novel role of MYLK‐L‐induced SOCE in increasing vascular permeability. MYLK‐L augmented SOCE by increasing endoplasmic reticulum (ER)‐plasma membrane (PM) junctions and STIM1 translocation to these junctions. Transduction of N‐MYLK domain (amino acids 1‐919 devoid of catalytic activity) into Mylk‐L –/– EC rescued SOCE to the level seen in control EC in a STIM1‐dependent manner. N‐MYLK‐induced SOCE augmented endothelial permeability without MLC‐P via an actin‐binding motif, DVRGLL. Liposomal‐mediated delivery of N‐MYLK mutant but not ∆DVRGLL‐N‐MYLK mutant in Mylk‐L –/– mice rescued vascular permeability increase in response to endotoxin, indicating that targeting of DVRGLL motif within MYLK‐L may limit SOCE‐induced vascular hyperpermeability.